Plasma wake-field acceleration of charged particles by selfmodulated long relativistic electron bunch - Karas, V.I.; Balakirev, V.A.; Fainberg, Ya.B.; Sotnikov, G.V.; Karas, I.V.; Levchenko, V.D. (Вопросы атомной науки и техники, 2000)
- High-amplitude plasma wake-waves are excited by high-density relativistic electron bunches (REB) moving in a plasma. The wake- fields can be used to accelerate charged particles, to serve as electrostatic wigglers in freeelectron plasma lasers (FEL), and also can find many other applications. The electromagnetic fields in the region occupied by the bunch control the dynamics of the bunch itself. In particular, the transverse forces cause a strong compression (pinching) of bunches having small transverse dimensions (kprb << 1, where kp = ωp/c, ωp is the plasma frequency, c is the light velocity, and rb is the radius of the bunch). This phenomenon is at the basis of operation of plasma lenses that can be used to focus ultrahigh energy particles. The longitudinal fields give rise to longitudinal modulation of an electron bunch. Specifically, an originally uniform bunch evolves into individual microbunches. This paper presents the results of 2.5-dimensional numerical simulation of both the modulation of long REB in a plasma and the excitation of wake fields by these bunches. The previous one-dimensional study has shown that the density profile modulation of a long bunch moving in plasma results in the growth of the wake wave amplitude. This is explained by the fact that the wake fields generated by microbunches being due to the evolution of the initially uniform bunch during the modulation, are coherent. The bunch modulation occurs at the plasma frequency. The present study is concerned with the REB motion, taking into account the plasma and REB nonlinearities. It is demonstrated that the radial REB dynamics exerts primary effect on both the REB self-modulation and the wake field excitation by the bunches formed.